Microstomia: entry made easy in no entry (with sectional tray and sectional denture). (9th July 2013) - Patel, Avani; Sethuraman, Rajesh; Prajapati, Paranjay; Patel, Jayanti R
Abstract : Reduced mouth opening or microstomia is a frequently encountered condition in the field of prosthodontics. Microstomia is a challenge for prosthodontics right from impression making till the insertion of the prosthesis. Making impressions in patients with microstomia is often cumbersome for both patient and operator. Standard impression procedures are not of any help due to limited mouth opening, so the modification of standard impression procedure is often necessary while treating such patients. Modification in denture prosthesis in the form of split denture, flexible denture, hinged denture, spring denture etc is needed to fulfil patients' demands. The present case displays the treatment of a patient with microstomia using modified impression tray design and maxillary split denture.